Underwater acoustic modeling and simulation - Etter, Paul C. (Taylor & Francis, 2013)
"The fourth edition of a bestseller examines the translation of physical understanding of sound in the sea into mathematical models that can simulate acoustic propagation, noise and reverberation in the ocean. The book includes extensive new material that addresses recent advances in inverse techniques and marine-mammal protection. It provides guidelines for selecting and using available propagation, noise and reverberation models. It also contains specific examples of each type of model are discussed to illustrate model formulations, assumptions and algorithm efficiency as well as instructive case studies that demonstrate applications in sonar simulation"--